Application of taguchi experiment design to reduce lignin contents of rice straw - Aprilyanti, Selvia; Suryani, Faizah; Azhari, Azhari (Universitas Ahmad Dahlan, 2020)
The Taguchi experimental design is an experimental design to get the quality of an object by providing the best design at the procurement stage. In this case, the Taguchi design was applied to reduce the contents of lignin from rice straw, where lignin is one of the rice straw components that useless which must be reduced or eliminated. Rice straw is composed of lignin, cellulose, and hemicellulose. The existence of lignin components that become a protective wall will inhibit the activity of cellulose, and hemicellulose for further processing to produce some fermented products such as bio-gas, bio-ethanol, bio-plastics, and others. The process of decreasing lignin content from rice straw is done in ozonolysis. In this study, Taguchi's experimental design analysis was using the application of MINITAB 14 which used for statistical calculation and create a level setting in a tabular form of arrays called orthogonal arrays. The orthogonal array matrix used is L9 (33 ) which states that the process was conducted 9 times with variations of 3 factors and 3 levels. The factors that influence the decrease in lignin levels include sample size, ozone flow rate, and contact time. The results showed that the smallest lignin content was carried out at 80 mesh sample size, the ozone flow rate of 3 L / Min, and contact time for 10 minutes.